Habitat disturbance trumps moonlight effects on the activity of tropical insectivorous bats. (3rd June 2021) - Appel, G.; López‐Baucells, A.; Rocha, R.; Meyer, C. F. J.; Bobrowiec, P. E. D.
Abstract: Changes in moonlight intensity can affect predation risk and induce changes in habitat use and activity of nocturnal species. However, the effect of moonlight on animal activity is rarely evaluated in human‐modified landscapes and can be of vital importance to understand possible changes in ecosystem services provided by light‐sensitive taxa, such as insectivorous bats. Fragmentation changes forest structure and affects light penetration across the landscape. In this case, the effects of fragmentation on bat activity can be modulated by cyclical variations of moonlight intensity. We acoustically quantified the activity of nine aerial insectivorous bat species in relation to moonlight at the Biological Dynamics of Forest Fragments Project, Central Amazonia. We aimed to understand species‐level variation in activity across habitats (continuous forest, fragments and secondary forest) at different temporal scales: lunar cycle, dark vs. bright nights and within nights. Amazonian aerial insectivorous bats responded more to habitat type than to moonlight, with two and six species showing reduced activity in fragments and secondary forest, respectively, compared to continuous forest. The lower activity in secondary forest suggests that despite c . 30 years of secondary forest regeneration, it is still less attractive as foraging habitat. An interactive effect of habitat type and moonlight on bat activity was most evident when contrasting dark and bright nights. Our results indicate that fragments have reduced bat activity on extremely bright nights, probably due to higher predation risk in small fragments. Species that emit constant‐frequency calls ( Pteronotus spp.) were the ones that most modulated their responses to habitat disturbance and moonlight. Otherwise, moonlight had little effect on hourly activity levels, irrespective of habitat type. Moonlight is capable of modulating the responses of some bat species in disturbed habitats, particularly in fragments. Abstract : We found that habitat disturbance was the main factor underlying decreases in aerial insectivorous bat activity, but moonlight accentuated reductions in activity for some species in forest fragments which is probably related to predation risk in small fragments. Pteronotus species were particularly sensitive to habitat disturbance and moonlight. In view of the recent increase of forest fragmentation and artificial light in the Brazilian Amazon, the protection of undisturbed forests is crucial for the conservation of light‐sensitive insectivorous bats.